2015
DOI: 10.9734/bjmmr/2015/11510
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Knowledge, Attitude and Practice of the Use of Insecticide- Treated Nets (ITNs) in Aba, Nigeria

Abstract: Background: Over the past decade, significant gains have been made in the implementation of malaria preventive measures in sub-Saharan Africa, including the distribution of insecticide treated nets (ITNs). These have been shown to cause a reduction in the incidence of malaria and other mosquito borne diseases. Methods: Knowledge, attitude and practices of the use of ITNs were critically evaluated in Aba, south eastern Nigeria from February to July, 2013. A cross-sectional study was conducted in four communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The knowledge and Use of Insecticide treated nets in rural communities where there is high incidence of malaria is vital f or malaria vector control and prevention (Ezeigbo et al, 2015) and Nigerian population mostly rural dwellers stand the risk of having malaria. This study provides data on the knowledge and use of insecticide treated nets among rural dwellers of Ivo local government in Ebonyi State.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge and Use of Insecticide treated nets in rural communities where there is high incidence of malaria is vital f or malaria vector control and prevention (Ezeigbo et al, 2015) and Nigerian population mostly rural dwellers stand the risk of having malaria. This study provides data on the knowledge and use of insecticide treated nets among rural dwellers of Ivo local government in Ebonyi State.…”
Section: Discussionmentioning
confidence: 99%
“…Various health authorities have made concerted ef f orts to promote the use of ITNs by rural dwellers, yet research has shown that the degree of awareness, ownership, and ef f ective use of ITNs by these individuals has varied f rom one area or region to the other (Ezeigbo et al, 2015, Sunday et al,. 2021.…”
Section: Introductionmentioning
confidence: 99%
“…respondents use beds net from this (65%) were using bed nets still currently, the remaining (35%) reported that they are not lucky to use it now due to lack of access (77%), lack of awareness (8%) and other reason (15%), and 62% drain stagnant water in their surroundings (Haile et al, 2015); Tanzania 68% of the households use ITNs (Sumari et al, 2016) and Nigeria, practices used to prevent mosquito bites, 299 (59.8%) use ITNs, 100 (20.0%) use insecticide sprays, 45 (9.0%) use window/door nets while 32 (6.4%) use repellants (Ezeigbo et al, 2015). Contrarily in other studies the ITNs utilization was poor in the study from Amhara National Regional State, Ethiopia, it was only 26.4% of the study participants that used ITN as malaria prevention and control method (Aderaw and Gedefaw, 2013); (Fuge et al, 2015), only 15.8% of 398 mothers owned at least one ITN.…”
Section: Discussionmentioning
confidence: 99%
“…Increased ITNs use throughout a community reduces transmission and thus has a more powerful impact than individual change (Teklehaimonot et al, 2007). It is also worth mentioning that even when knowledge is a predictor of ITN use; it may not assure protection from malaria unless there is proper use and strong adherence (Ezeigbo et al, 2015). The main focus of the elimination program is the scaling-up of parasitological and entomological surveillance through early diagnosis (by microscopy and/or rapid diagnostic tests) and prompt treatment, and vector control activities, i.e.…”
Section: Introductionmentioning
confidence: 99%